Persepsi Masyarakat terhadap Perbankan Syariah:: Studi Kasus Nasabah Bank Syariah Indonesia - Firda Durrotun Nafisah (Jurnal Akuntansi dan Bisnis Syariah, 2024)
This study aims to explore public perceptions of Islamic banking. The research method used is qualitative research, where data is collected through in-depth interviews with Islamic bank customers. The results of this study indicate that although there is a growing awareness of Islamic banking as an alternative that is in accordance with Islamic principles, there is still a lack of understanding of its core concepts among the public. This study identifies challenges such as limited education about Islamic banking, lack of socialization, and product complexity that hinder the growth of Islamic banking. This study suggests that innovative and proactive educational efforts are needed to develop more accessible products and increase public acceptance of Islamic banking services.